2015
DOI: 10.1002/anie.201500372
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio‐ and Stereoselective Hydrosilylation of Internal Thioalkynes under Mild Conditions

Abstract: A general and mild hydrosilylation of thioalkynes is described. With the cationic catalyst [Cp*Ru(MeCN)3 ](+) and the bulky silane (TMSO)3 SiH, a range of thioalkynes underwent smooth hydrosilylation at room temperature with excellent α regioselectivity and syn stereoselectivity. DFT calculations provided important insight into the mechanism, particularly the unusual syn selectivity with the [Cp*Ru(MeCN)3 ](+) catalyst. The sulfenyl group in the substrates was found to provide important chelation stabilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…[1] Tr ansition-metal-catalyzed hydrosilylation reactions have made great success over the past few decades. [2] In comparison with Ru, Rh, Pt, and others,m anganese-catalyzed hydrosilylation has largely lagged behind (Scheme 1a). As early as in 1982, Yates,for the first time,reported Mn 2 (CO) 10 catalyzed hydrosilylation of acetone,a lbeit only in 5% GC yield.…”
Section: Xiaoxu Yang and Congyang Wang*mentioning
confidence: 99%
“…[1] Tr ansition-metal-catalyzed hydrosilylation reactions have made great success over the past few decades. [2] In comparison with Ru, Rh, Pt, and others,m anganese-catalyzed hydrosilylation has largely lagged behind (Scheme 1a). As early as in 1982, Yates,for the first time,reported Mn 2 (CO) 10 catalyzed hydrosilylation of acetone,a lbeit only in 5% GC yield.…”
Section: Xiaoxu Yang and Congyang Wang*mentioning
confidence: 99%
“…Hydro-silylations of alkynes enable a most straightforward and atom-economic synthesis of alkenylsilanes in the presence of the noble metal catalysts Ru, Rh, and Pt. 2 4 Only few protocols rely on the use of inexpensive and environmentally benign 3d base metal catalysts. 5 Despite the recent progress in the field, the precise control of regioselectivity and stereoselectivity remains a challenge of utmost importance.…”
mentioning
confidence: 99%
“…[8] According to the literature, only a few successful examples have been reported that involve gold cation and substrates bearing sulfur-containing moieties . [9,10] Particularly, the activation of thioalkynes using gold cations has not been reported. Some key challenges of gold-catalyzed thioalkyne activation include the: A) sulfur coordination to gold due to its nucleophilicity, preventing the desired electrophilic activation of the alkyne; B) unknown reactivity of the C–C triple bond due to the conjugation of sulfur’s 3p electrons to the alkyne p-system, resulting in different activation modes (Scheme 1B).…”
mentioning
confidence: 99%